2022
DOI: 10.1039/d2cp04434j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a ternary Bi2O3/CQDs/rGO photocatalyst to active peroxymonosulfate for the removal of tetracycline hydrochloride

Abstract: In this paper, the ternary Bi2O3/carbon quantum dots (CQDs)/reduced graphene oxide (rGO) photocatalyst was synthesized by hydrothermal method for the degradation of tetracycline hydrochloride. The Bi2O3/CQDs/rGO composites showed stronger visible...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…1, the crystal structures of Bi 2 O 3 , g-C 3 N 4 and BO/CN were determined by XRD. The diffraction peaks of two samples can easily correspond with Bi 2 O 3 , which were in agreement with the standard card (JCPDS Card number: 71-2274, P 21/ c (14) space group) with major peaks at 2 θ = 25.7°, 26.8°, 27.4°, 33.3° and 46.3° corresponding to the diffractions of (002), (−112), (−121), (−202) and (040), respectively, 40 which indicated that Bi 2 O 3 was obtained. The two main diffraction peaks of g-C 3 N 4 were observed at position 2 θ = 13.2° and 27.5°, corresponding to the (100) and (002) plane, respectively.…”
Section: Resultssupporting
confidence: 85%
“…1, the crystal structures of Bi 2 O 3 , g-C 3 N 4 and BO/CN were determined by XRD. The diffraction peaks of two samples can easily correspond with Bi 2 O 3 , which were in agreement with the standard card (JCPDS Card number: 71-2274, P 21/ c (14) space group) with major peaks at 2 θ = 25.7°, 26.8°, 27.4°, 33.3° and 46.3° corresponding to the diffractions of (002), (−112), (−121), (−202) and (040), respectively, 40 which indicated that Bi 2 O 3 was obtained. The two main diffraction peaks of g-C 3 N 4 were observed at position 2 θ = 13.2° and 27.5°, corresponding to the (100) and (002) plane, respectively.…”
Section: Resultssupporting
confidence: 85%